Health status of inmates of homes for persons with disabilities in Central India: a cross-sectional study - Padole, Wandana H.; Patil, Sonali; Narlawar, Uday W.; T. Nimje, Ashish (International Journal Of Community Medicine And Public Health, 2023)
Background: Disability is not just a health problem or attribute of individuals, but it reflects difficulties that individuals may experience in physical movements and interaction with society. Studies have indicated that persons with disabilities may experience a poorer health and quality of life than the general population. Inmates most commonly suffer from mental disorders with/without multiple disabilities. Musculoskeletal disorders and injuries were the most common morbidities identified. Methods: A descriptive cross-sectional study to assess health status was conducted in various homes for persons with disabilities in Central India in 130 subjects out of which 64.62% were male and 35.38% were female. Results: In present study, maximum i.e., 18 (13.85%) of study subjects were having fatigue followed by cold 15 (11.54%), throat pain 13 (10%), Generalized pain (not otherwise specified) 12 (9.23%), pain in abdomen 7 (5.38%) at the time of examination. Health status reveals that maximum number 49 (37.69%) of study subjects were having anaemia followed by 15 (11.54%) rhinitis. Conclusions: Predominant morbidities observed in study subjects are underweight, anemia, and hypertension while refractive error, diabetes mellitus these were present in few study subjects. Regular health check-ups or camps should be organized for diagnosis and management of health problems of persons with disabilities.